Comparison of quantitative mineralogy and sequential leaching for characterization of Ni in workplace dust collected at a stainless steel operation. Issue 12 (2nd December 2021) - Kelvin, Michelle; Verpaele, Steven; Leybourne, Matthew; Layton-Matthews, Daniel; Vermeir, Pieter
Abstract: Based on epidemiological records of workers at Ni operations, regulatory guidelines commonly target specific Ni compounds for setting exposure limits. Thus, reliable methods of Ni speciation in airborne dust samples are required for effective monitoring of workplace exposure. Zatka sequential leaching has been routinely performed industry-wide since the 1990s for characterization of Ni in dust samples; however, limitations related to leaching kinetics have been identified, and optimization of the methodology is required to improve accuracy of data. In this study, Ni characterization of dust collected from a stainless steel operation was performed using Zatka sequential leaching (original and modified protocols) and quantitative mineralogy (QEMSCAN), a method novel to the field of industrial hygiene. Mineral analysis was also performed on bulk material collected from selected work areas at the plant. The results are compared with the objective of identifying opportunities to optimize the methods for characterizing dust that is unique to stainless steel manufacturing. The quantitative mineralogical analysis determined that the Ni dust is composed of oxidic Ni (chromite and trevorite, >80% of the Ni in most samples) and metallic Ni (Ni-Fe alloy), and the results were validated against chemical assays and alternate methods of mineral characterization. In contrast, the original Zatka method erroneously identified soluble Ni as a major Ni contributor, whereas the modified Zatka method identified sulfidic Ni. The mineralogy identified Ni-barren dust and grain sizes and liberation of individual Ni compounds as potential factors that can affect leaching selectivity. Clearly, for any sequential leaching method to be useful for these workplaces, they should be optimized by including reference materials that are representative of Ni substances present at stainless steel operations (chromite, trevorite, and Ni-Fe alloy). Improving methods of sequential leaching is important because the resolution of quantitative mineralogical techniques diminishes at <3 μm (respirable dust fraction). We recommend that quantitative mineralogy be performed in parallel with methods of sequential leaching to provide a robust system of characterization.